THE INFLUENCE OF MACHIAVELLIAN LOVE OF MONEY ON THE ETHICAL PERCEPTION OF ACCOUNTING STUDENTS (A STUDY ON ACCOUNTING STUDENTS OF GORONTALO STATE UNIVERSITY) - Siti Rahma; Tri Handayani Amaliah; Amir Lukum (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the influence of Love of Money and Machiavellian traits on the ethical perceptions of accounting students. The independent variables in this study are Love of Money (X1) and Machiavellian traits (X2), while the dependent variable is the ethical perception of accounting students (Y). This study employs a quantitative approach using a survey method. The population of this study consists of accounting students at Universitas Negeri Gorontalo, with a total sample of 32 respondents selected using purposive sampling technique. Data were collected through the distribution of questionnaires via Google Forms and analyzed using descriptive statistical analysis and multiple linear regression with the assistance of SPSS software.The results of the study indicate that partially, Love of Money has a positive and significant effect on the ethical perceptions of accounting students. This suggests that students perceive money as a motivation to achieve success in an ethical manner. Meanwhile, Machiavellian traits have a negative and significant effect on the ethical perceptions of accounting students, indicating that the higher the tendency toward manipulation and self-interest orientation, the lower the level of ethical perception. Simultaneously, Love of Money and Machiavellian traits have a significant effect on the ethical perceptions of accounting students.